Análise preliminar dos riscos ambientais da Bacia do Rio Uraim, em um Município da Amazônia Oriental - Sardinha, Aline Souza; Ventura, Katia Sakihama (International Workshop for Innovation in Safe Drinking Water, 2022)
This work proposes a preliminary analysis of the environmental risks caused in the Uraim River basin, in which the river that names it is used as a source of water supply in the municipality of Paragominas, State of Para, Brazil. The method used was deductive, as it is based on two true premises: (1) The river basins are altered by human actions, (2) the quality of the source of water supply becomes a challenge for the operators of water treatment plants. (WTP). The predominant activities in the municipality are livestock, agriculture, mining, logging and trade in services. The results showed that the Uraim River basin has high deforestation of native vegetation. Twelve areas of high and very high risk of a mass movement and flooding were identified, which are associated with the disorderly expansion of the urban area, combined with the geomorphology and geology of the region. It is recommended that the Uraim River basin committee be implemented, so that its watershed management can take place, in the incessant search for improving the quality of source of water supply, so that it is feasible to capture, treat and distribute safety drinking water to the population.